Linguistic argumentation, a guide for the study of vowel lengthening in Aymara - Huayhua Pari, Felipe (2019)
In this paper we present the vowel lengthening in the framework of the methodological state of the grammatical argumentation according to Botha (1970). From twenty isoglosses that separate the northern Aymara (Umasuyu) from the southern Aymara (Orcosuyo), lengthening is one of the more representative isoglosse. By its nature, lengthening is not a phoneme but the product of five factors to take into account: 1) elition of continuous consonants between equal and different vowels, 2) lengthening in a group of internal consonants, 3) lengthening in suffixes with those consonants, 4) lengthening in compound words and 5) reanalysis as false lengthening.